Psychological Determinants of Decision-making Through Religious Vocation in View of the Theory of L.M. Rulla SJ - Soiński, Borys Jacek (Filozofia Chrześcijańska, 2013)
This article is based on research on the decision-making process about religious vocation. The progress of this process depends on many conditions and factors. The article analyzes the important role of freedom in decision-making. Determinants of vocational decisions are shown in the background theory of self-transcendence consistency by L.M. Rulla. The consistency of the vocation and the decisions of the progress growth in vocation depend on three essential components of personality: values, psychophysiological needs and attitudes. The task of psychology is to determine the personality traits of a candidate on the stage of formation and determine its developmental potential. Diagnosis of internal integration of the candidate to serve the selection or assistance that should be given to him before deciding sustainable.